Freely chosen cadence is increased across repeated bouts of submaximal ergometer cycling - Hansen, E.; Schmidt, A.; Madsen, J. (Journal of Science and Cycling, 2022)
The aim of the present study was to investigate whether the phenomenon of repeated bout rate enhancement occurs during submaximal ergometer cycling. In the present context, repeated bout rate enhancement is defined as an increase of the freely, or spontaneously, chosen cadence during repeated bouts of pedalling. This is for example relevant to study since cadence, and thereby the described phenomenon, can affect physiological and biomechanical responses.